Highly polarized [GeOTe3] motif-driven structural order promotion and an enhanced second harmonic generation response in the new nonlinear optical oxytelluride Ba3Ge2O4Te3. Issue 1 (9th December 2021) - Sun, Mengran; Zhang, Xingyu; Li, Chunxiao; Liu, Wenhao; Lin, Zheshuai; Yao, Jiyong
Abstract : A new NLO-active oxytelluride, Ba3 Ge2 O4 Te3, was successfully synthesized by using Ba2 ZnGe2 O7 as a parent model. Both experiments and theoretical calculations show that Ba3 Ge2 O4 Te3 is a promising NLO material with well-balanced properties. Abstract : The hybrid anion strategy has been illustrated to be an effective way to design and synthesize high-performance nonlinear optical (NLO) crystals. Herein, a new NLO-active oxytelluride with a highly polarized [GeOTe3 ] unit, Ba3 Ge2 O4 Te3, has been successfully synthesized. Driven by the distorted [GeOTe3 ] motif, this compound exhibits interesting structural order promotion with its parent model Ba2 ZnGe2 O7 (BZGO). Moreover, on the basis of inheriting the polarization structure of BZGO, the Ba3 Ge2 O4 Te crystal possesses an enhanced second harmonic generation (SHG) response benefiting from the partial replacement of O with the more polarized Te. Remarkably, the experimental results and theoretical calculations reveal that Ba3 Ge2 O4 Te3 has the potential to be a promising infrared (IR) NLO material, encompassing a strong SHG response with good phase matchability, wide band gap, high laser damage threshold (LDT), and large birefringence of 0.14@2.09 μm (5.7× AGSe, 10× BZGO) which overcomes the drawback of the small birefringence of AGSe. This work demonstrates that a highly polarized [GeOTe3 ] motif can be used as a new basic building block (BBB) for IR NLO materials, providing a new idea for the exploration of new functional oxytellurides.